Biodegradation of Ammonium by Suspended and Immobilized Cells of Acinetobacter sp. Y1 - Lv, Yongkang; Yang, Jieyong; Liu, Yuxiang (Asian Journal of Chemistry, 2013)
A heterotrophic nitrifier Y1 was isolated from the activated sludge of a coking wastewater treatment. According to the result, the strain confirmed the final ammonium removal efficiency ca. 95.66 % in 120 h, DNA sequencing and homologous analysis of 16 s rRNA gene identified that strain Y1 belonged to Acinetobacter sp. Poly(vinyl alcohol) was used as a gel matrix to immobilize Acinetobacter sp.Y1 by repeated freezing and thawing. The factors affecting ammonium removal of immobilized cells were studied and the results showed that the immobilized cells could tolerate a higher ammonium concentration than that of suspended cell. Storage stability and reusability tests revealed that the ammonium removal functions of immobilized cells were steady after respected use for 20 times or storing at 4 ºC for 50 d. All these experimental results showed that immobilized Acinetobacter sp. strain Y1 possessed a good application potential in the treatment of coking wastewater.